Economic Analysis of International Law Contributions to the XIIIth Travemünde Symposium on the Economic Analysis of Law (March 29-31, 2012) - Oeter, Stefan; Voigt, Stefan; Eger, Thomas (Mohr Siebeck, 2014)
Ökonomische Analyse des internationalen Rechts. Beiträge zum XIII. Travemünder Symposium zur ökonomischen Analyse des Rechts (29.-31. März 2012).
PublicationDate: 20140604
Keywords: Völkerrecht -- Internationalisierung -- Globalisierung -- Institutionenökonomik -- Array